(untitled) (International Journal of Physiotherapy, 2016)
Background: Abnormal altered scapular position during rest or motion have been termed as Scapular Dyskinesia. Scapula Dyskinesia Type-2 is one type of dyskinesia in which there is a visual prominence of entire medial border of scapula that occurs due to weakness of the serratus anterior and tightness of posterior shoulder joint capsule that results in reduction in glenohumeral flexion and abduction, resulting in decreased acromial elevation. This type of dyskinesia is commonly seen in Secondary impingement of shoulder. Rehabilitation generally begins and focused on axio-humeral and scapula- humeral than axio-scapular muscle. Early application of closed kinetic exercises on scapular stabilization and its effect of application on scapular dyskinesia type 2 is unknown. The study was proposed to find the effect of scapular stabilization exercise for type 2 Scapular Dyskinesia in subjects with shoulder impingement. Methods: An experimental study design, 7 male patients with mean age 37 years diagnosed with Shoulder impingement associated with Type 2 scapular dyskinesia were included in the study. The protocol includes closed kinematic chain exercises (scapula clock), Black burn exercises, Sleepers stretch, and thera band exercises aimed to balance force couple of upper, lower trapezius and serratus anterior. Duration of intervention was 3 sessions per week for 2 weeks. Outcome measurements such as Lateral scapular slide test and SPADI were measured pre and post interventions. Results: Analysis using Paired ‘t’ test as a parametric test found that there is statistically significant difference p<0.000 when pre to post interventions means were compared within the groups showing significant improvement in post SPADI and lateral scapular slide test. Conclusion: It is concluded that Scapula stabilization exercise protocol found to be effective in Scapular type-2 Dyskinesia.